TEKNIK PEER-REVIEW MELALUI GOOGLE DOCS: ALTERNATIF PIRANTI KOLABORASI DALAM MENULIS - Sholihah, Umi (Widya Wacana: Jurnal Ilmiah, 2018)
AbstractThe digital era requires us to always be creative and innovative. As an educator, we must also be creative and innovative to find new innovations in learning. One of the innovations in learning is by utilizing the Google Docs application. This paper is based on classroom action research on the use of the Google Docs application to support the use of Peer-Review technique in writing for English department students of Widya Dharma University of Klaten. The results of the study show that the Peer-Review technique by utilizing the Google Docs application in writing can 1) train students to think critically, observantly, and thoroughly when reviewing their friends’ writing which can automatically improve their own writing skills; 2) increase the ability to collaborate and work together to have global competitiveness in the 21st century; 3) motivate students to be active in completing writing assignments; 4) make learning in the classroom more meaningful by creating a more lively classroom situation; 5) make students feel more enjoying and active in writing; 6) save paper usage; 7) provide allowance to students for whenever and wherever they want to review the writing of their friends without having to be bound by time and place when learning to write in class; 8) can boost the sharpness of student analysis so that it can be used also in other fields of study.Keywords: Peer-Review Technique, Google Docs Application, Writing Skills AbstrakEra digital menuntut kita untuk selalu berinovasi dan mampu menyesuaikan diri dengan perkembangan yang ada. Sebagai seorang pendidik, kita juga harus selalu kreatif dan inovatif untuk mencari inovasi baru dalam pembelajaran. Salah satu inovasi dalam pembelajaran adalah dengan memanfaatkan aplikasi Google Docs. Makalah ini berdasarkan penelitian tindakan kelas tentang pemanfaatan aplikasi Google Docs untuk mendukung penggunaan teknik Peer-Review dalam pembelajaran menulis mahasiswa Pendidikan Bahasa Inggris Universitas Widya Dharma Klaten. Hasil penelitian menunjukkan teknik Peer-Review dengan memanfaatkan aplikasi Google Docs dalam pembelajaran menulis dapat 1) melatih mahasiswa untuk berfikir kritis, jeli, dan teliti saat menelaah tulisan temannya yang secara otomatis dapat meningkatkan kemampuan menulis mereka sendiri; 2) meningkatkan kemampuan berkolaborasi dan bekerja sama agar memiliki daya saing global di abad ke-21; 3) memotivasi mahasiswa untuk aktif dalam menyelesaikan tugas menulis; 4) membuat pembelajaran di kelas menjadi lebih berarti dengan menciptakan situasi di kelas lebih hidup; 5) membuat mahasiswa merasa lebih menikmati dan aktif pada pembelajaran menulis; 6) menghemat penggunaan kertas; 7) memberikan kelonggaran kepada mahasiswa untuk kapanpun dan dimanapun mereka ingin mereview tulisan temannya tanpa harus terikat waktu dan tempat saat pembelajaran menulis di kelas; serta 8) dapat mendongkrak ketajaman analisis mahasiswa sehingga dapat dimanfaatkan pula pada bidang-bidang kajian lain.Kata kunci: Teknik Peer-Review, Aplikasi Google Docs, Kemampuan Menulis